Synthesis and properties of novel trifunctional epoxy triglycidyl of 4‐(4‐aminophenoxy)phenol with high toughness. Issue 16 (7th January 2015) - Shang, Chengyuan; Zhao, Xiaojuan; Sun, Baogang; Yang, Xin; Zhang, Ying; Huang, Wei
ABSTRACT A trifunctional epoxy containing oxyphenylene unit, triglycidyl of 4‐(4‐aminophenoxy)phenol (TGAPP) was synthesized and characterized. The chemical structure of TGAPP was confirmed with FTIR and 1H‐NMR. DSC analysis revealed that the reactivity of TGAPP with curing agent 4, 4′‐diaminodiphenylsulfone (DDS) was significantly lower than that of triglycidyl para‐aminophenol (TGPAP). Rheological analysis showed that the processing window of TGAPP/DDS was 20°C wider compared with that of TGPAP/DDS. The thermal and mechanical properties of cured TGAPP/DDS were investigated and compared with those of the cured TGPAP/DDS. Experimental results showed that, due to the introduction of oxyphenylene unit, the heat resistance and flexural strength were slightly reduced, while the tensile strength and impact strength were enhanced. SEM also confirmed that the introduction of oxyphenylene unit could enhance the toughness of the TGAPP/DDS as evident from ridge formation. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41878.